2021
DOI: 10.1088/1755-1315/892/1/012088
|View full text |Cite
|
Sign up to set email alerts
|

Scheme to support coconut replanting program on smallholder plantation

Abstract: Coconut plantations are dominated by smallholders characterized by limited land area, low productivity, and low added value. The low productivity is partly due to the old age of the plants. The performance of coconut plantations can be improved, among others, through replanting smallholder plantations, but the implementation is still low, mainly due to financing constraints. This study aims to develop a financing scheme to support coconut replanting programs in smallholder plantations. The analysis used is Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Coconut development in Indonesia has been extensively researched, starting from the cultivation system with smallholder coconut rejuvenation related to seed system development, capacity building of farmers and farmer organizations, and technology support [24]. Control of fungi that cause fruit drop [25] and pests that reduce coconut productivity [26].…”
Section: Coconut Agro-industry Development In Indonesiamentioning
confidence: 99%
“…Coconut development in Indonesia has been extensively researched, starting from the cultivation system with smallholder coconut rejuvenation related to seed system development, capacity building of farmers and farmer organizations, and technology support [24]. Control of fungi that cause fruit drop [25] and pests that reduce coconut productivity [26].…”
Section: Coconut Agro-industry Development In Indonesiamentioning
confidence: 99%
“…The seed component was a major issue to be tackled by the government, aimed at achieving higher productivity. Wulandary et al [62] forecasted a strategy for accelerating the coconut-replanting program that mainly consisted of the development of the seed system through nursery establishment, seed distribution, and planting and cultivation management. This instrument could be a fundamental policy for strengthening the coconut oil position amid international market competition with other oil commodities.…”
Section: Long-term Relationship Impact On Indonesian Coconut Oil Exportsmentioning
confidence: 99%
“…Muyengi (2017) reported that new seedlings planted per hectare decreased by 75 percent between 1999 and 2014, at the household level in Tanzania. Wulandari and Alouw (2021) reiterated that replanting coconuts are a sure method for improved performance in small holdings in Indonesia. The One can readily motivate diffusion in rational choice-theoretic terms even when no information about consequences is provided (Banerjee, 1992).…”
Section: Community Coconut Farm Schools (Cfs)mentioning
confidence: 99%